2005
DOI: 10.1021/jp0558775
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cations from Dicyclopropylidenemethane and Its Octamethyl Derivative

Abstract: The radical cations of dicyclopropylidenemethane (2) and its octamethyl derivative (2-Me 8 ) are prone to rearrangements into those of (2-methylallylidene)cyclopropane (2a) and its octamethyl derivative (2a-Me 8 ), respectively, by opening one three-membered ring. In contrast to the radical cations of bicyclopropylidene (1) and its octamethyl derivative (1-Me 8 ), 2 •+ and 2-Me 8 •+ are stable to opening of the second ring, because in this case the resulting species would be a non-Kekulé hydrocarbon with a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Assuming that polyfluoroarene RAs possess the close rates of disappearing via the geminate recombination we can estimate the rate of 2 −• decay via the parallel chemical process using a fluorescence decay curve for some acceptor giving a stable RA. 34 Such approach is approximate, so the use of several reference RAs increases accuracy of estimate. We use as a reference the fluorescence decay curves, I 1 (t), obtained for alkane solutions of 1 and hexafluorobenzene.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that polyfluoroarene RAs possess the close rates of disappearing via the geminate recombination we can estimate the rate of 2 −• decay via the parallel chemical process using a fluorescence decay curve for some acceptor giving a stable RA. 34 Such approach is approximate, so the use of several reference RAs increases accuracy of estimate. We use as a reference the fluorescence decay curves, I 1 (t), obtained for alkane solutions of 1 and hexafluorobenzene.…”
Section: Resultsmentioning
confidence: 99%
“…The assumed decay should lead to a charged product and its recombination with a counterion does not induce fluorescence. The rate constant of this process was determined from the ratio of the kinetic curves to the corresponding curves for TFB solutions as described in [11]. The decay activation energy of ≈3.5 kcal/mol was determined from the temperature dependence of rate constant k(Т ) shown in Fig.…”
Section: Time Resolved Magnetic Field Effect As a Methods Of Studying mentioning
confidence: 99%
“…Contrastingly, the radical cation of bicyclopropylidene (and its octamethyl derivative) is stable to opening of the second ring, since the resulting species would be a non-Kekule hydrocarbon with a quartet ground state. 104 The radical cation of Dewar benzene and its ring-opening to the hexamethylbenzene radical cation was first observed using ESR by Rhodes. 105 In a more recent study, this species was generated and observed by optical spectroscopy in cryogenic matrices to which it reveals itself by a charge resonance band at 600 nm, in fact very similar in shape and position to that observed for the related radical cation of norbornadiene.…”
Section: Organic Radicalsmentioning
confidence: 99%